2012
DOI: 10.1007/s00360-012-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum: a key factor in cardiac contractility of sea bass Dicentrarchus labrax and common sole Solea solea during thermal acclimations

Abstract: This study investigated the effects of acclimation temperature upon (i) contractility of ventricular strips (ii) calcium movements in ventricular cardiomyocytes during excitation-contraction coupling (ECC), and (iii) the role of the sarcoplasmic reticulum (SR) in myocardial responses, in two marine teleosts, the sea bass (Dicentrarchus labrax) and the common sole (Solea solea). Because of the different sensitivities of their metabolism to temperature variation, both species were exposed to different thermal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Our study on the fresh water catfish showed that at 20°C, SR contribution is involved at 0.2 and 0.4 Hz pacing frequencies with cardiac force falling by approximately 21% after caffeine treatment and cardiac force increasing by approximately 40% and 18% at 0.2 and 0.4 Hz pacing frequencies after adrenaline treatment. This is in contrast to previous studies which indicated that the SR involvement is limited to low pacing frequency (0.2 Hz) (Shiels and Farrell, 1997;Shiels et al, 1998;Imbert-Auvray et al, 2013). Furthermore, our study showed that the SR-Ca 2+ release contribution is involved at The number of ventricular preparation in each series was 6. d Non significant as compared with control.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our study on the fresh water catfish showed that at 20°C, SR contribution is involved at 0.2 and 0.4 Hz pacing frequencies with cardiac force falling by approximately 21% after caffeine treatment and cardiac force increasing by approximately 40% and 18% at 0.2 and 0.4 Hz pacing frequencies after adrenaline treatment. This is in contrast to previous studies which indicated that the SR involvement is limited to low pacing frequency (0.2 Hz) (Shiels and Farrell, 1997;Shiels et al, 1998;Imbert-Auvray et al, 2013). Furthermore, our study showed that the SR-Ca 2+ release contribution is involved at The number of ventricular preparation in each series was 6. d Non significant as compared with control.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous studies have extensively examined and discussed the significance of SR-Ca 2+ release to ventricular force development in marine ectothermic animals at cold and warm temperature (Shiels and Farrell, 1997;Shiels et al, 1998Shiels et al, , 2002Vornanen et al, 2002;Imbert-Auvray et al, 2013). Results of these studies indicate that the role of SR is secondary to that of the sarcolemmal Ca 2+ influx in supplying Ca 2+ for the force development.…”
Section: Discussionmentioning
confidence: 88%
“…For example, the effects of adrenaline were mainly observed in cold-acclimated teleosts (perch: Tirri and Ripatti 1982;Tirri and Lehto 1984;rainbow trout: Graham and Farrell 1989;Keen et al 1994). Moreover, SR-Ca 2+ loading and mobilisation have been shown to depend on species and thermal acclimation (Imbert-Auvray et al 2013).…”
mentioning
confidence: 98%
“…From a functional standpoint, this indicates that the cardiac contraction at 12°C depends more on the mobilisation efficiency of intracellular Ca 2+ stored in the SR than on an extracellular Ca 2+ source. This increase in the SR channel contribution to Ca 2+ mobilisation, as usually found in cold-acclimated fish (Imbert-Auvray et al, 2013;Keen et al, 1994;Shiels et al, 2002;Vornanen, 1996Vornanen, , 1998 could be explained by a SR proliferation in heart cells (Bowler and Tirri, 1990;Keen et al, 1994Keen et al, , 2017Shiels and Farrell, 1997;Shiels et al, 2011), a higher ryanodine sensitivity (Vornanen et al, 2005) and/or a partial (or complete) inactivation, due to cold, of the SL channels/exchanger allowing extracellular Ca 2+ influx into the cells (Vornanen, 1998;Vornanen et al, 2002).…”
Section: Discussionmentioning
confidence: 86%